Pengaruh Country of Origin, Brand Image, Electronic Word of Mouth, dan Celebrity Endorser terhadap Keputusan Pembelian Konsumen Produk Skincare Somethinc - Harsoyo, Titik Desi; Utami, Dyah Septi (Yayasan Lentera Avanya Nagari, 2024)
This research aims to analyze the effect of country of origin, brand image, electronic word of mouth, and celebrity endorser on purchasing decisions for Somethinc skincare products. The sample in this study was 100 respondents who had purchased and used Somehinc skincare products. The data collection method used was a survey with questionnaires as the research instrument. The instrument test results stated that the data in this study was proven to be valid and reliable. In the classical assumption test, it was revealed that the data in this study were normally distributed and produced a regression model that was free from multicollinearity and heteroscedasticity. Hypotheses test using multiple linear regression proves that country of origin and electronic word of mouth have a significant effect on purchasing decisions, while brand image and celebrity endorsers do not have a significant effect on purchasing decisions for Somethinc skincare products. The research results have implications for future research to further explore the variables that play a role in determining purchasing decisions. Practical implications are given to Somehinc product manufacturers and similar companies to formulate strategies that influence consumer purchasing decisions.